Segmentation of Colour Video Sequences Using the Fast Marching Method - Steć, Piotr (Zielona Góra: Oficyna Uniwersytetu Zielonogórskiego)
This thesis is related to the problem of segmentation of video sequences. Automatic video segmentation plays important role in many applications such as: object oriented coding of digital video, remote surveillance, interactive multimedia presentations and video editing. The main problem considered in this work is ability of segmentation sequences acquired with a moving camera which parameters are unknown. As a main analytical tool the Fast Marching Method was used as an active contour propagation method. Since it is very general algorithm, it was necessary to adopt it to the problem that was considered in this thesis.
Keywords: segmentacja; sekwencje wizyjne; kompresja; algorytm szybkiej propagacji; propagacja; rozprawa doktorska; telekomunikacja; nauki techniczne; przetwarzanie obrazów